2020
DOI: 10.14341/ket12239
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the population in Russian Federation about iodine deficiency, its effects and methods for prevention of iodine deficiency disorders.

Abstract: Background: Throughout all territory of Russian Federation has been confirmed absence of iodine deficiency of varying severity. Chronic iodine deficiency leads to irreversible defects in the intellectual and physical development of children, thyroid gland diseases, including such severe manifestations as functional autonomy and iodine-induced thyrotoxicosis and reproductive disorders. Aims: To assess the awareness of Russians about the effect of iodine deficiency on health and the need to use iodized sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
0
0
4
Order By: Relevance
“…По результатам анкетирования взрослого населения Чеченской Республики, проведенного в рамках данного исследования, утвердительные ответы о регулярном использовании йодированной соли в питании были получены от 26,7% респондентов, что в более чем 2 раза отличается от истинной доли домохозяйств с йодированной солью в питании (11,7%). Таким образом, по результатам исследования отмечаются низкая информированность населения о проблеме йододефицита (осведомлены только 57%) и еще более низкая приверженность респондентов к проведению массовой йодной профилактики, что в целом согласуется с данными других опросов населения РФ [ 16 ]. Этот анализ также демонстрирует, что в рамках эпидемиологических исследований и для мониторинга эффективности программ профилактики ЙДЗ необходимо использовать методики качественной или количественной оценки содержания йода в пищевой соли, а не данные опросов населения.…”
Section: Discussionunclassified
“…По результатам анкетирования взрослого населения Чеченской Республики, проведенного в рамках данного исследования, утвердительные ответы о регулярном использовании йодированной соли в питании были получены от 26,7% респондентов, что в более чем 2 раза отличается от истинной доли домохозяйств с йодированной солью в питании (11,7%). Таким образом, по результатам исследования отмечаются низкая информированность населения о проблеме йододефицита (осведомлены только 57%) и еще более низкая приверженность респондентов к проведению массовой йодной профилактики, что в целом согласуется с данными других опросов населения РФ [ 16 ]. Этот анализ также демонстрирует, что в рамках эпидемиологических исследований и для мониторинга эффективности программ профилактики ЙДЗ необходимо использовать методики качественной или количественной оценки содержания йода в пищевой соли, а не данные опросов населения.…”
Section: Discussionunclassified
“…Iodine deficiency may interrupt biological functions and cause the development of endocrinological diseases such as goiter, hypothyroidism and cognitive impairment. A study by the National Research Center for Endocrinology of the Ministry of Health of the Russian Federation showed that annually, 1.5 million adult patients and 600 thousand children with endocrinological disorders receive medical care in the Russian Federation [9]. In monetary terms, the cost of treatment exceeds 250 billion rubles, which is 5 times more than the amount needed to organize measures to prevent all iodine deficiency disorders in the Russian Federation.…”
Section: Iodine Deficiency Statisticsmentioning
confidence: 99%
“…Результаты опроса показали, что 60,4% опрошенных используют в быту йодированную соль, только половина (52,73%) респондентов, проживающих на территории Западной Сибири, потребляют йодированную соль. Однако очень небольшое количество (57 человек) жителей Западной Сибири приняли участие в опросе [17].…”
Section: обсуждение основного результата исследованияunclassified